2005
DOI: 10.1523/jneurosci.2001-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament Polymer Transport in Axons

Abstract: Neurofilament proteins are known to be transported along axons by slow axonal transport, but the form in which they move is controversial. In previous studies on cultured rat sympathetic neurons, we found that green fluorescent protein-tagged neurofilament proteins move predominantly in the form of filamentous structures, and we proposed that these structures are single neurofilament polymers. In the present study, we have tested this hypothesis by using a rapid perfusion technique to capture these structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…Conversely, the molecular basis of the apical polarization of keratin IFs in simple epithelial cells is currently unknown. However, unlike in the case of keratinocyte IFs [37] or neurofilament IFs [38] that move on microtubules, the steady-state, polarized, distribution of keratin IF in simple epithelial cells is not affected by long and extensive depolymerization of MTs, such as in the case of ATP depletion in tissue culture cells, ischemia-reperfusion in kidney proximal tubules [17] or long incubations in anti-microtubular drugs [39]. Moreover, in simple epithelia IFs are not perinuclear, with the exception of a few lateral bundles coming in contact with the lateral aspect of the nucleus (Fig.…”
Section: Location Location Location: Apical Distribution Of Intermementioning
confidence: 98%
“…Conversely, the molecular basis of the apical polarization of keratin IFs in simple epithelial cells is currently unknown. However, unlike in the case of keratinocyte IFs [37] or neurofilament IFs [38] that move on microtubules, the steady-state, polarized, distribution of keratin IF in simple epithelial cells is not affected by long and extensive depolymerization of MTs, such as in the case of ATP depletion in tissue culture cells, ischemia-reperfusion in kidney proximal tubules [17] or long incubations in anti-microtubular drugs [39]. Moreover, in simple epithelia IFs are not perinuclear, with the exception of a few lateral bundles coming in contact with the lateral aspect of the nucleus (Fig.…”
Section: Location Location Location: Apical Distribution Of Intermementioning
confidence: 98%
“…Many membranous organelles and protein complexes are normally transported anterograde within neuronal axons to the presynaptic terminal, and details of the motors, adaptors and cargoes have received significant attention (Hirokawa and Takemura, 2005;Goldstein and Yang, 2000) In contrast, much less is known about the regulation of transport of non-membrane bound particles in neurons (Brown, 2003). For example, mRNAs and proteins associated with the mRNA and cytoskeletal polymers require transport motors (presumably kinesin-related) and associated proteins for their delivery to dendrites and axons (Bassell et al, 1998;Hirokawa, 2006;Yan and Brown, 2005;Wang and Brown, 2002;Galbraith and Gallant, 2000). Identification of the specific motors and associated motor proteins that participate with Us9 in viral capsid and DNA anterograde transport is extremely important but likely to be a challenging task (Baas and Qiang, 2005).…”
Section: How Viral Dna Is Axonally Transportedmentioning
confidence: 99%
“…Studies on cultured neurons using live-cell fluorescence imaging have demonstrated that neurofilament polymers move rapidly and intermittently along axons in both anterograde and retrograde directions (Roy et al, 2000;Wang et al, 2000;Wang and Brown, 2001;Uchida and Brown, 2004;Yan and Brown, 2005). The instantaneous rate of movement is fast, with peak velocities of up to 3.5 m/s, but the overall rate is slow because the movements are interrupted by prolonged pauses (Brown, 2000(Brown, , 2003Brown et al, 2005;Trivedi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%